1997
DOI: 10.1007/s004420050076
|View full text |Cite
|
Sign up to set email alerts
|

Wipfelkrankheit : modification of host behaviour during baculoviral infection

Abstract: Infection with an endoparasite frequently alters host behaviour. This study provides the first quantification of larval behaviour in a baculovirus/ Lepidoptera system, and attempts to assess the ecological consequences of behavioural modification during infection. Larvae of the moth Mamestra brassicae (Lepidoptera: Noctuidae) exhibited higher rates of dispersal in the laboratory and field when infected with Mamestra brassicae nuclear polyhedrosis virus (MbNPV) than did uninfected larvae. They adopted positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 32 publications
2
128
1
2
Order By: Relevance
“…These authors proposed that the modern baculovirus may have acquired ptp gene from an ancestral host and that this gene was selectively maintained because it increases virus transmission. These results support the Goulson (1997) hypothesis.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…These authors proposed that the modern baculovirus may have acquired ptp gene from an ancestral host and that this gene was selectively maintained because it increases virus transmission. These results support the Goulson (1997) hypothesis.…”
Section: Introductionsupporting
confidence: 88%
“…The baculovirus life cycle is peculiar because it produces two types of infectious progenies with different functions, but essential to natural propagation. The occluded form of the virus (PDV) is responsible for the transmission from insect to insect, while the nonoccluded form (BV) is responsible for transmission from cell to cell, in a same individual (systemic infection) (GRANADOS;FEDERICI, 1986 According to Castro et al (1999) after 80 to 100 hours of infection, there is the discoloration of insect's tegument in several hosts. After death, the insect usually breaks up easily, releasing great amount of polyhedrons into the atmosphere, which in turn will infect new larval populations of the host insect.…”
Section: Introductionmentioning
confidence: 99%
“…Since first described by Hofmann [2], many studies have demonstrated that baculovirus-infected larvae (i) disperse over larger areas than uninfected larvae (hyperactivity) and (ii) die at elevated positions, typically the tops of trees or plants (tree-top disease) [2][3][4][5][6][7][8][9][10][11][12][13]. These behavioural manipulations have been described for several baculovirus-larvae systems and may increase viral spread, as virus will rain down plant foliage.…”
Section: Baculoviruses: Masters Of Manipulationmentioning
confidence: 99%
“…Occlusion-derived viruses (ODVs), which are occluded in occlusion bodies (OBs), transmit virus from insect to insect via oral infection, whereas budded viruses (BVs) spread infection to neighboring cells (16,37). At the late stage of infection, a markedly enhanced locomotion behavior of infected larvae is observed (15,25), which is followed by a dramatic degradation of the host cadaver (11).…”
mentioning
confidence: 99%